EVIDENCE-BASED LIBRARY MANAGEMENT: URGENSI DAN TANTANGAN PENERAPANNYA DI INDONESIA - Yaniasih, Yaniasih (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2014)
Evidence - based library management ( EBLM ) is a relatively new concept in the library management. This concepthas been implemented in several countries to improve the quality of library services, the quality of librarians, and thequality of publications in field of library and information science. This study discusses the urgency of implementingEBLM in Indonesia and its challenges. The study use literature and secondary data method. The secondary datawhich used consists of the availability and the access to scientific evidences as well as the quantity and quality ofhuman resources. Results of the data and theory triangulation was then analyzed descriptively. The results arguethat EBLM is important to be implemented in Indonesia and might be a potential to overcome the existing problemsof librarianship, particularly in LIPI. The implementation will face some challenges such as the limited scientificevidences and the ideology of librarian or library leader. The study also provides several recommendations tosupport EBLM implementation on national scale, library organizations, and professional organizations.